THE ANALYSIS OF “ALICE’S ADVENTURES IN THE WONDERLAND “BY LEWIS CAROLL IN ENGLISH AND UZBEK TRANSLATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines how different languages influence through, “Alice’s adventures in the wonderland “by Lewis Caroll. This work also translated into diverse range of languages such as Uzbek, Russian, English and so on. When it comes to the novel,it goes into facing  variations  in two languages ,particularly Uzbek and English languages.In one word we can see a lot of distinctions in this  work   during analayzing through uzbek and english languages. Alice’s adventures in Wonderland translated as “Alisaning mo’jizalar o’lkasidagi sarguzashtlari” by M .Zohidova in the mutolaa app .Additionally ,the novel has been trnslated into 175 languages, with Japanese having  the most editions.